2003
DOI: 10.1002/jnr.10747
|View full text |Cite
|
Sign up to set email alerts
|

JLK isocoumarin inhibitors: Selective γ‐secretase inhibitors that do not interfere with notch pathway in vitro or in vivo

Abstract: gamma-Secretase activity is involved in the generation of Abeta and therefore likely contributes to the pathology of Alzheimer's disease. Blocking this activity was seen as a major therapeutic target to slow down or arrest Abeta-related AD progression. This strategy seemed more doubtful when it was established that gamma-secretase also targets other substrates including Notch, a particularly important transmembrane protein involved in vital functions, at both embryonic and adulthood stages. We have described p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 64 publications
0
29
1
Order By: Relevance
“…Control explants consisted of medium containing DMSO (1 l/ml). In addition, we tested three other ␥-secretase inhibitors: JLK6 (5, 10, and 25 M) (27), L685458 (L6; 1, 10, 25, and 50 M) (28), and Compound 1 (C1; 25, 50, and 100 M) (4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control explants consisted of medium containing DMSO (1 l/ml). In addition, we tested three other ␥-secretase inhibitors: JLK6 (5, 10, and 25 M) (27), L685458 (L6; 1, 10, 25, and 50 M) (28), and Compound 1 (C1; 25, 50, and 100 M) (4).…”
Section: Methodsmentioning
confidence: 99%
“…8C). Finally, we compared the DAPT effects in the lung with that of JLK6, an isocoumarin-based serine protease known to inhibit ␥-secretase activity of other substrates but not of Notch (27). Analysis of NICD, Sox2, and Titf1 expression confirmed that Notch cleavage was preserved and that proximal-distal patterning was undisturbed in JLK6 -treated explants (5-25 M) (supplemental Fig.…”
Section: Fgf10 Induces Expression Of Notch1 and Jag Ligands But Not mentioning
confidence: 97%
“…This is best illustrated by the lack of spreading of the plasma membrane that characterizes multinucleated macrophages. In contrast, JLK2, a PS inhibitor that inhibits the cleavage of APP but not Notch, 21 failed to inhibit the fusion of rat alveolar macrophages (data not shown). This confirmed that JLK2, unlike DAPT and DupE, affects ␥-secretase activity differently, and suggested that it might target different substrates, or different domains of the same substrates within the ␥-secretase complex.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, the pro-apoptotic signal by the secretase inhibitor may be more potent in the modulation of neutrophil apoptosis than the anti-apoptotic signal of Aβ. It was found that the direct addition of Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) to the cultured neutrophils failed to exert an anti-apoptotic effect on the neutrophils even though it has been shown that Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in fibrillary state induces O 2 − and Aβ(1-42) production [3]. Therefore, it is possible that Aβ(1-40) can inhibit neutrophil apoptosis in the monomer state.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), Aβ(1-40), Aβ(1-42), Aβ , and Aβ(40-1) were purchased from Bachem AG. The zVADfmk, zDEVD-fmk, zIETD-fmk, β-secretase inhibitor II (z-VLL-CHO), β-secretase inhibitor III (H-EVNstatineVAEF-NH 2 ), γ-secretase inhibitor I ( Z -Leu-Leu-NorLeue-CHO), γ-secretase inhibitor II (Boc-VI-NHCH(CH 3 )-COCF 2 -CO-NHVI-OCH 3 ), γ-secretase inhibitor XI (7-amino-4-chlroro-3-methylisocoumarin), phosphoinositide 3-kinase (PI 3-K) inhibitor (LY294002), phospholipase C (PLC) inhibitor (U73122), phospholipase A 2 (PLA 2 ) inhibitor (MAFP), and protein kinase C (PKC) inhibitor (calphostin C and Go6976) were obtained from Calbiochem.…”
Section: Reagentsmentioning
confidence: 99%